Avoiding timescale bias in assessments of coastal wetland vertical change. (31st January 2018) - Breithaupt, Joshua L.; Smoak, Joseph M.; Byrne, Robert H.; Waters, Matthew N.; Moyer, Ryan P.; Sanders, Christian J.
Abstract: There is concern that accelerating sea‐level rise will exceed the vertical growth capacity of coastal‐wetland substrates in many regions by the end of this century. Vertical vulnerability estimates rely on measurements of accretion and/or surface‐elevation‐change derived from soil cores and/or surface elevation tables (SETs). To date there has not been a broad examination of whether the multiple timescales represented by the processes of accretion and elevation change are equally well‐suited for quantifying the trajectories of wetland vertical change in coming decades and centuries. To examine the potential for timescale bias in assessments of vertical change, we compared rates of accretion and surface elevation change using data derived from a review of the literature. In the first approach, average rates of elevation change were compared with timescale‐averaged accretion rates from six regions around the world where sub‐decadal, decadal, centennial, and millennial timescales were represented. Second, to isolate spatial variability, temporal comparisons were made for regionally unique environmental categories within each region. Last, comparisons were made of records from sites where SET‐MH stations and radiometric measurements were co‐located in close proximity. We find that rates vary significantly as a function of measurement timescale and that the pattern and magnitude of variation between timescales are location‐specific. Failure to identify and account for temporal variability in rates will produce biased assessments of the vertical change capacity of coastal wetlands. Robust vulnerability assessments should combine accretion rates from multiple timescales with the longest available SET record to provide long‐term context for ongoing monitoring observations and projections.